Acute Effect of Citrulline Malate Supplementation on Upper-Body Resistance Exercise Performance in Recreationally Resistance-Trained Men. Issue 11 (November 2018) - Gonzalez, Adam M.; Spitz, Robert W.; Ghigiarelli, Jamie J.; Sell, Katie M.; Mangine, Gerald T.
Abstract : Abstract: Gonzalez, AM, Spitz, RW, Ghigiarelli, JJ, Sell, KM, and Mangine, GT. Acute effect of citrulline malate supplementation on upper-body resistance exercise performance in recreationally resistance-trained men. J Strength Cond Res 32(11): 3088–3094, 2018—To investigate the effect of citrulline malate (CM) supplementation on upper-body resistance exercise performance, 12 recreationally resistance-trained men (21.4 ± 1.6 years; 163.0 ± 46.2 cm; 85.0 ± 12.4 kg) underwent 2 testing sessions administered in a randomized, double-blind fashion. During each visit, participants were provided either 8 g of CM or a placebo (PL) 40 minutes before beginning a standardized warm-up and initiating a barbell bench press resistance exercise protocol consisting of 5 sets of 15 repetitions at 75% 1 repetition maximum with 2-minute rest intervals. Participants were instructed to complete as many repetitions as possible until either reaching 15 repetitions or muscular failure. Total number of repetitions performed and power output were recorded for each set. Subjective measures of energy, focus, fatigue, and perceived exertion, along with muscle thickness of the triceps brachii, were assessed before and after exercise. Significant ( p ⩽ 0.05) main effects for time were observed for all variables except for subjective feelings of energy ( p = 0.085). A group × time interaction ( F = 2.86, p = 0.034, n 2 = 0.21) was observed for repetitions performed, where participants performed more ( p = 0.015) repetitions on set 3 during PL (5.7 ± 1.2 repetitions) compared with CM (4.6 ± 1.2 repetitions). However, during set 4, participants tended ( p = 0.089) to perform more repetitions during CM (4.8 ± 1.8 repetitions) compared with PL (4.3 ± 1.3 repetitions). No other differences were observed between trials. Supplementation with 8 g of CM 40 minutes before the barbell bench press resistance exercise protocol did not increase exercise performance, augment the muscle swelling response to training, or alter subjective measures of focus, energy, and fatigue in recreationally resistance-trained men.